2016
DOI: 10.1016/j.mcn.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNAs in human post-mortem amyotrophic lateral sclerosis spinal cords provides insight into disease mechanisms

Abstract: Amyotrophic lateral sclerosis is a late-onset and terminal neurodegenerative disease. The majority of cases are sporadic with unknown causes and only a small number of cases are genetically linked. Recent evidence suggests that post-transcriptional regulation and epigenetic mechanisms, such as microRNAs, underlie the onset and progression of neurodegenerative disorders; therefore, altered microRNA expression may result in the dysregulation of key genes and biological pathways that contribute to the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 96 publications
(144 reference statements)
3
78
0
Order By: Relevance
“…Postmortem human spinal cord tissues from ALS subjects were assessed to identify aberrantly regulated microRNAs [55]. Expression and systems biology analyses revealed that mature miRNAs are globally reduced and miRNA processing is altered.…”
Section: The Role Of Epigenetic Regulation In Als and Ftdmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmortem human spinal cord tissues from ALS subjects were assessed to identify aberrantly regulated microRNAs [55]. Expression and systems biology analyses revealed that mature miRNAs are globally reduced and miRNA processing is altered.…”
Section: The Role Of Epigenetic Regulation In Als and Ftdmentioning
confidence: 99%
“…For example, miR-206 was consistently altered during the course disease in SOD1 -Gly93Ala mice and increased in the circulation of a small cohort of ALS patients [173]. Furthermore, exploring therapeutic strategies targeting pathogenic miRNAs in ALS is further supported by the recent report on aberrantly regulated miRNAS in sporadic ALS discussed above [55]. Manipulating miRNAs has the advantage to alter multiple gene targets simultaneously using a single drug, but the disadvantage of non-specific binding to other miRNAs resulting in deleterious off-target effects.…”
Section: The Role Of Epigenetic Regulation In Als and Ftdmentioning
confidence: 99%
“…The identification of miRNAs has enhanced our understanding of transcriptional and translational regulation, opening new avenues for investigating molecular mechanisms contributing to numerous diseases. Of particular interest are diseases associated with perturbations in RNA processing, such as amyotrophic lateral sclerosis (ALS) …”
mentioning
confidence: 99%
“…A large number of miRNAs are known to be dysregulated in various ALS tissues, with a global downregulation of miRNAs observed in motor neurons of patients with ALS . How these dysregulated miRNAs influence the disease onset, progression, and severity still requires experimental validation.…”
mentioning
confidence: 99%
See 1 more Smart Citation